Sustainable Development Goals-Oriented Project: Teachers' Digital Comics on Quality Education and Environmental Issues - Ilhan, Genc Osman; Tekin, Eda; Ozdemir, Fatih (MDPI, 2026)
This study explores how teachers interpret the Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education) and SDG 13 (Climate Action), as pedagogical frameworks and how they translate these goals into pedagogical practice through the design of digital comics. Adopting a qualitative case study design, the research was conducted within the scope of a professional development project entitled Comics of Values and the Environment. The participants consisted of 36 in-service teachers who took part in expert-led training focusing on sustainability education and digital comics design. Data were collected through semi-structured interviews with 12 teachers, teachers' self-produced digital comics, and researcher observations of the design process. All qualitative data were analyzed using inductive content analysis. The findings indicate that prior to the training, teachers' understanding of the SDGs was largely superficial and remained at the level of general awareness. Following the sustainability-oriented training and design-based activities, teachers developed more concrete and pedagogically grounded interpretations of SDG 4 and SDG 13. Quality education was increasingly conceptualized as a holistic process extending beyond academic achievement to include critical thinking, creativity, multimodal literacy, and lifelong learning. Climate action was interpreted not merely as raising awareness but as improving responsibility, agency, and action-oriented learning. Teachers perceived digital comics as effective pedagogical tools for making abstract environmental issues more concrete, enhancing student engagement, and supporting inquiry-based learning. Despite challenges related to technical infrastructure, curriculum constraints, and the need to simplify complex sustainability concepts, the digital comic design process functioned as a form of professional learning. It supported teachers' reflective thinking, creative problem-solving, and pedagogical agency. The study demonstrates that sustainability-oriented digital comics design can support the translation of global sustainability goals into meaningful classroom practices and highlights the importance of design-based professional development in education for sustainable development.
Keywords: sustainable development goals; SDG 4 (quality education); SDG 13 (climate action); digital comics; sustainability education; teacher professional development; EDUTAINMENT; COMPETENCES; Science & Technology - Other Topics; Environmental Sciences & Ecology